SLOPE STABILITY ANALYSIS OF EMBANKMENT AND EXCAVATION SLOPES AND DESIGN OF GROUND ANCHOR REINFORCEMENT OF TANAH PUTIH MINES HOUSING COMPLEX, TANJUNG ENIM, SUMATRA SELATAN - VANESSA BANGUN (NIM: 15013100), SHERLY
Tanah Putih Mines Housing Complex is built to provide housing for all workers of the mine to be able to commute with ease from their homes to the workplace. Due to the steep contour conditions of the site, slope stability analysis is crucial. Slope failure is generally caused by the greater driving force and overturning moment compared to the retaining force and resisting moment of the soil. There are several methods of reinforcement for slope stabilization. In this final project, there will be two critical locations that will be observed, an embankment slope and an excavation slope. The embankment slope has a safety factor above the minimum requirement, and hence, does not require soil reinforcements. However, the excavation slope has a safety factor below the minimum and thus requires soil reinforcement. The soil reinforcement used to stabilize the slope are ground anchors. The ground anchors are used to withstand the tensile forces from the natural load of the soil itself and also external loads. The Ground anchor passes the forces from the structure, in this final project a shotcrete facing is used, to the ground where it is anchored. There are two designed ground anchors with free lengths of 10 m respectively, 3 strands each, and equal bonded lengths of 13 m.